PENGUJIAN TECHNOLOGY ACCEPTANCE MODEL (TAM) DAN THEORY PLANNED BEHAVIOR (TPB) - Jurica Lucyanda (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam 45, 2010)
The purpose of this study is to examine the factors that determine intention of the accounting student to adopt internal software My Quick Accounting System (My QAS) in economic faculty of Islamic University “45” Bekasi. To identify the factors that affect intention to adopt internal software using a research model based on Technology Acceptance Model (TAM) and Theory of Planned Behavior (TPB). The behavior factors that using in this study are perceived usefulness, perceived ease of use, attitude, subjective norms, self efficacy, and technology support. The respondent in this study that only the accounting students who have participated in accounting computer course. This study using the survey method for data collection (personally administrated questionnaires).The results indicate that the accounting student’s intention to adopt My QAS determine by behavior factors such as: perceived usefulness, perceived ease of use, attitude, subjective norms and technology support.